Analisis Psikologi Tokoh Bahar dalam Novel Janji Karya Tere Liye - Irfan Rahadian Vieri; Jumiati Jumiati; Muhammad Hanafi; Suhartini Khalik (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The purpose of this study is to analyze the psychological aspects experienced by the character Bahar in Tere Liye's novel Janji using a qualitative descriptive method to describe the data in the form of stimuli, responses, and reinforcements experienced by the character. The research data consists of quotes that show the presence of stimuli, responses, and forms of reinforcement that appear throughout Bahar's journey in the story. The data source comes entirely from Tere Liye's novel Janji. The data collection techniques used include coding techniques to mark relevant quotes and close reading techniques to read and understand the text in depth. Data analysis was carried out by reading the entire novel to understand the context of the events involving Bahar, and then coding each finding related to stimuli, responses, and reinforcements. Next, the findings were analyzed using B. F. Skinner's behaviorism theory to examine the relationship between the character's received stimuli, the responses they exhibited, and the reinforcements that influenced their behavioral changes. Based on the research findings, it was discovered that Bahar's behavior is highly influenced by environmental factors, including interactions with those around him, which elicit various specific responses. These responses then undergo changes or reinforcement based on the experiences he has, indicating that Bahar's behavior is shaped by a combination of external and internal influences.